Seroprevalence and risk factors of Toxoplasma gondii and Neospora caninum infection in black goats in Yunnan Province, Southwestern China - Hu, Xiao-Hui; Xie, Shi-Chen; Liang, Qin-Li; Sun, Li-Xiu; Li, Zhao; Yang, Jian-Fa; Zhu, Xing-Quan; Zou, Feng-Cai; He, Jun-Jun (Frontiers in Veterinary Science, 2022)
Toxoplasma gondii and Neospora caninum are two obligate intracellular protozoan parasites that can cause reproductive failure and production losses. To date, there is no data of T. gondii and N. caninum seroprevalence in black goats in Yunnan Province, southwestern China. In the present study, a total of 734 serum samples were collected from black goats in four different counties of Yunnan Province. 734 and 590 serum samples were examined for antibodies against T. gondii and N. caninum by using MAT and indirect ELISA, respectively. A total of 123 and 76 samples were T. gondii-positive and N. caninum-positive, respectively. The overall seroprevalence of T. gondii in black goats was 16.76% (123/734, 95% CI: 14.06-19.46) with the titer ranged from 1:25 to 1:3200. The seroprevalence of N. caninum was 12.88% (76/590, 95% CI: 10.18-15.58). There was significant difference in seroprevalence of N. caninum in different regions (P <0.01, 2 = 30.63) and age groups (P <0.05, χ2 = 11.85). Significant differences in seroprevalence of T. gondii were observed in different regions (P <0.05, χ2 = 9.21) and different gender groups (P <0.01, χ2 = 12.29). Results of seroprevalence of T. gondii and N. caninum indicated that T. gondii and N. caninum were prevalent parasites in black goats in Yunnan Province. This is the first report of seroprevalence of T. gondii and N. caninum in black goats in Yunnan Province. The results of this study indicated that some measures should be taken to control these two parasites and to reduce economic losses to the livestock industry in Yunnan province.